Implementasi Problem Based Learning Berbantuan Papan Statistika untuk Meningkatkan Hasil Belajar Siswa Kelas VII - Vina, Alvina Aulia; Hadi, Muhammad Sofian; Sundi, Venni Herli; Sugiyanti, Sugiyanti (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
In the process of teaching and learning activities, especially in mathematics subjects, there are still many students who get low grades. This is because students feel bored with the monotonous models, methods and learning strategies in class. Apart from that, the lack of use of creative and innovative learning media makes student learning outcomes low. This research aims to improve students' mathematics learning outcomes by implementing PASTA learning media. The type of research used is Class Action (PTK). This Classroom Action Research was conducted on 28 students in class VII-1 at SMP Lab School FIP UMJ. The instruments used in this research were observation, documentation and tests. The results of this action research show that implementing PASTA learning media can improve students' mathematics learning outcomes. This can be seen in cycle I, before using learning media, the average score for class VII-1 students was 65, but after action was taken in cycle II using PASTA learning media, the average score for students was 84. As well as an increase in learning outcomes. By implementing the PASTA learning media, the percentage of completeness can also be seen. The percentage of completion in cycle I was 54%, but in cycle II it increased to 93%. Both the percentage of learning completeness and the average student score in cycle II have met the specified criteria. Keywords: Instructional Media, Statistics board, Mathematics learning outcomes